4(f-6)=-52

Simple and best practice solution for 4(f-6)=-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(f-6)=-52 equation:


Simplifying
4(f + -6) = -52

Reorder the terms:
4(-6 + f) = -52
(-6 * 4 + f * 4) = -52
(-24 + 4f) = -52

Solving
-24 + 4f = -52

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 4f = -52 + 24

Combine like terms: -24 + 24 = 0
0 + 4f = -52 + 24
4f = -52 + 24

Combine like terms: -52 + 24 = -28
4f = -28

Divide each side by '4'.
f = -7

Simplifying
f = -7

See similar equations:

| 3x^2-4x-m=0 | | 14X+28=15X+20 | | (8-7)*2=12 | | 5(3s+8)=145 | | 6(2l+2)=24 | | (4n-20)-n=n+12 | | (e+4)*5=35 | | 2(a-3)=28 | | 5(a-8)=75 | | 9-5-8+10= | | (q-7)*3=123 | | (e+4)*2=16 | | 3x-75=1 | | 9a-5a-8a+10a= | | x^3+10x^2+16x+1=0 | | 4t^2+8t-1=0 | | 9x+9=90-9x+27 | | (-9r^3+2r-1)-(-5r^2+r+8)= | | x(3x+4)=8 | | 3=-2x*27 | | 3x-2x+9x=0 | | n-15=35 | | 3(5x-2)=11 | | (3x+4)(x-1)+54=0 | | 3x+c=300 | | 5sin(x)=2cos(x) | | X*3+2x=42 | | -3+5/3x=4 | | 3x+7=379 | | W=5x+2 | | 40+a=2(16+a) | | Y=200x-80 |

Equations solver categories